Taking the Licensure Examination for Teachers: Why a hard job for BEED Graduates? - Pineda, Susan; Fernandez, Charissa May; Revidizo, Jerome (International Journal of Arts, Sciences and Education, 2026)
This paper explores the Licensure Examination for Professional Teachers (LEPT) experience of Bachelor of Elementary Education (BEED) examinees in 2014-2018 because this is one of the pressing concerns of the department in consonance to higher accreditation level of the department. This study attempted to determine the factors that make it a hard job for the graduates to take and pass the board examination. Data were obtained from the PRC results and the survey questionnaire administered to the respondents inclusive of five years since these years were the most challenging periods for the results obtained. This study adopted the descriptive qualitative research design in investigating the problem to describe the trend of the results in each year and identify the factors that make it a hard job for the examinees in taking and passing the board exams. In this study, findings revealed that among the five factors, LEPT content is moderately related to the LEP results attendance similar to attendance in the review classes. Meanwhile, preparation for the examination and the program curriculum were also claimed by the participants moderately related and do not affect them very much in taking the teachers’ board examination. It is only the Course Preference/Career Choice with 3.96 composite mean that make it difficult in taking and passing the board examination a hard job. Majority of the graduates claimed that education course is not their course preference that made them reluctant to enhance their skills and abilities in the first three years of their stay in college. Still, others were not very serious when studying the program. They enrolled and took the program because this was the choice of their parents and other members of the family. LEPT results varies for the general education and professional education. Institutional passing rate is generally higher when compared to the national passing rate in 2014 and 2016 but lower in 2015 and 2017. It can be gleaned from the data that the general education passing rate varies. It dropped in 2015, increased in 2016, then dropped again in 2017. Meanwhile, the passing rate in professional education increased in 2016 but dropped constantly from 2016 to 2017. The results can be attributed to the fact that the examinees found the items in the general education easier and can be easily recalled. Graduates of the BEED Program who failed and got low ratings in the board examination took the program lightly. They were not able to attend regularly the review classes, hence, were not able to focus and put themselves on the proper mind set as they took the examination. Graduates who completed the degree were not able to deepen their love and passion for teacher education program that indicate evidence of complexity of real-life dreams and aspirations.